Air‐gap flux‐oriented vector control of dual stator induction generator used in wind energy conversion system with novel 13‐zone time optimized space vector‐based hybrid bus clamping PWM. (14th December 2021) - Chatterjee, Shantanu; Mukherjee, Arghya; Das, Abhijit
Abstract: This work presents a novel speed sensor less air‐gap flux‐oriented vector control of dual stator induction generator (DSIG) used for grid connected, variable speed wind energy generation system. The DSIG consists of two stator windings electrically separated by an angle of 30° with dissimilar pole numbers, which are in the ratio of 1:3. This arrangement offers reduced magnetic core saturation and less harmonics in stator currents, which results into reduced stator winding losses. Moreover, presence of two stator windings makes DSIG suitable to be used in high power application. In conventional rotor‐flux‐oriented control, the rotor flux is oriented along the d‐axis of the rotor winding. But the rotor flux is not easily accessible. Air‐gap flux‐oriented vector control (AGFOVC) is advantageous as compared to conventional vector control because the air‐gap flux is easily accessible and does not require any special arrangement for the measurement of variables. Moreover incorporation of this novel speed sensor less air‐gap flux‐oriented vector control also eliminates the use of speed encoder as the rotor speed is estimated from the machine terminal variables. Elimination of speed encoder not only reduces the cost of the overall system but also nullifies the error due to mismeasurement of speed and enhances control flexibility and robustness. As a result of which robustness of the system increases. Here, two separate converters are used for the two stator windings of the machine. And the converter switching's are being performed by space vector‐based novel dwell time optimized 13‐zone hybrid PWM. This special PWM results in better harmonic performance, reduced torque pulsation, and minimal switching loss. The simulation of the overall system is performed in MATLAB environment and the simulated results are validated experimentally using dSPACE controller board DS1104. Close proximity in simulated and experimental waveforms justifies the effectiveness of the proposed work. Abstract : In this manuscript a novel air‐gap flux oriented vector control of dual stator induction generator (DSIG) used for grid connected, variable speed wind energy generation system has been presented. This control scheme not only proves to be more efficient in terms of speed estimation but also increases robustness of the overall system. The power converter is being controlled by the use of novel 13‐zone hybrid PWM which results into minimization of line current ripple, torque pulsation and switching energy loss. The overall control scheme is being simulated in MATLAB environment and the results obtained in simulation are validated through appropriate experimental setup. More over instead of using any DC motor as prime mover an artificial wind generation unit is being constructed to form the experimental test bench.